IMPLEMENTASI METODE EXTREME PROGRAMMING DALAM PERANCANGAN SISTEM INFORMASI PEMBAYARAN SPP PADA SMK ERA PEMBANGUNAN MENGGUNAKAN PAYMENTS GATEWAY MIDTRANS - Nurhayati; Munawaroh (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Recording data for student tuition payments is still done manually, namely using proof of payment of triplicate receipts written by the cashier using handwriting and recapitulating the names of students who have paid, the process takes a long time and is written using handwriting. The large number of SPP transactions from various students of different vocational education levels every day caused cashiers to have difficulty writing names and student identities which in writing receipts were written manually using handwriting, this caused SPP data collection to be inaccurate. The difficulty of the treasurer validating the data of students who have paid the tuition fee is due to the handwriting of the tuition cashier, which sometimes the treasurer has difficulty reading the child's name. The SPP payment information system provides accurate and well-documented recording information. The SPP payment information system makes it easier for treasurers to recap financial reports. Reducing the level of data duplication in recording SPP payment reports so that it does not take time or there is no additional time in recapping SPP reports.